The Role of Youth in Child Literation Education - Risdayati Risdayati (HK-Publishing, 2022)
AbstractEducation can be a reasonably necessary basis for everyone, the initial foundation for each living life. Education can not only be obtained in school, but education and learning can be obtained from other people. One of them is teenagers. Teenagers at this time have an essential role in being responsible for preparing the next generation of children better. Like Rumah Ilmu youth, they set up a study group to increase the spirit of literacy among children. The lack of children’s interest in literacy is one of the reasons teenagers in Suka Mekar Village set up a Study Group called Rumah Ilmu. With the existence of the Science House, it is hoped that it can become a change for the village so that more children will like things about literacy such as reading, writing, and arithmetic.Keywords:Education, Youth, Literacy, Science House AbstrakPendidikan dapat menjadi landasan yang cukup penting bagi setiap orang, yang dapat menjadi landasan awal bagi setiap individu dalam menjalani kehidupan. Pendidikan tidak hanya dapat diperoleh di sekolah tetapi pendidikan dan pembelajaran dapat diperoleh dari orang lain. Salah satunya adalah remaja, remaja saat ini memiliki peran penting dalam bertanggung jawab untuk mempersiapkan generasi penerus anak yang lebih baik. Seperti pemuda Rumah Ilmu, mereka membentuk kelompok belajar untuk meningkatkan semangat literasi terhadap anak-anak. Minimnya minat anak terhadap literasi menjadi salah satu alasan para remaja di Desa Suka Mekar mendirikan Kelompok Belajar yang diberi nama Rumah Ilmu. Dengan adanya Rumah Ilmiah ini diharapkan dapat menjadi perubahan bagi desa agar semakin banyak anak yang menyukai hal-hal tentang literasi seperti membaca, menulis dan berhitung.Kata Kunci: Pendidikan, Pemuda, Literasi, Science House